Invasion reversal by front transitions and their implications for ecosystem management. (December 2022) - Ferré, M.A.; Bennett, J.J.R.; Novoplansky, A.; Meron, E.
Abstract: Alien species often become invasive by triggering the growth of pathogens that exert a strong negative effect on the native species. Using an extended Lotka–Volterra plant competition model that includes pathogen dynamics with a strong Allee effect we identify a bistability range of counter-propagating fronts representing invasion and recovery dynamics. The fronts differ in the levels of the pathogen in the front zone; high, beyond the Allee threshold for the invasion front and low, below that threshold for the recovery front. Invasion reversal is then studied as induced transitions from invasion fronts to recovery fronts. The study suggests managing invasion by local manipulations in the front zone that increase the Allee threshold and thereby reverse the front from invasion to recovery. We demonstrate numerically direct and indirect manipulations of this kind. Graphical abstract: Highlights: The concepts of front bifurcations and transitions are applied to invasion reversal. Pathogen-driven plant invasion is studied using an extended Lotka–Volterra model. Allee effect in pathogen dynamics results in coexisting invasion and recovery fronts. Local increase of the Allee threshold can shift an invasion front to a recovery front. Allee-threshold manipulations can be used as novel practices for invasion management.